PATIENT CHOICE IN THE POST-SEMASHKO HEALTH CARE SYSTEM - Sergey Shishkin; Alexandra Burdyak; Elena Potapchik (National Research University, Higher School of Economics, 2013)
The opportunity for patient choice in the health care system in CIS countries was created by the partial destruction of the referral system and the development of paid medical services. The data of two population surveys conducted in Russia in 2009 and 2011 show that patient choice of medical facility and physician is taking place in the post-Semashko health care system, and it is not restricted to the area of paid medical services. However for the majority of population the choice of medical facility and physician is not a necessity. Part of reason for patient choice is caused by the failure of the patient referral system to ensure the necessary treatment. For some Russian citizens, the choice of health care provider is a means to obtain better quality care, and in this respect the enhancement of patient choice is leading to the improved efficiency of the emerging health care system. – – . , 2009 2011 , - , . . . , , .
Keywords: I10; I11; 330; health care; Semashko system; patient choice; Russia